Meng-alay dalam Dunia Maya: Disorder Bahasa dalam Cyberspace - ARUM CANDRA (Universitas Muhammadiyah Yogyakarta, 2012)
The appearance of The cyberspace as a virtual world without borders, prompting the appearance of the many communities that contestation each other in order to reach their existence. Alay is one of the many groups in virtual world that has arisen many controversy. One of the controversy that impact is creation language Alay that swerve from axiom language in general and language cyber in particular. From this point, Alay have participated in creating a ketidakberaturan (disorder) language in cyberspace. Keywords: cyberspace, Alay, cyber language, language disorder